An unusual presentation of COVID-19: Acute pancreatitis - Kandasamy, Sathish (Ann Hepatobiliary Pancreat Surg, 2020)
Novel COVID-19 infectious disease typically presents with pulmonary symptoms like cough, shortness of breath, and fever. However, gastrointestinal manifestations of COVID-19 are increasingly being recognized and drawn significant attention. We report an atypical case of acute pancreatitis in a patient with SARSCoV2 infection. CT scan of the abdomen showed findings suggestive of acute interstitial edematous pancreatitis with a CT severity index was 3. HRCT chest revealed multifocal ground glass opacities in both lungs with a CORADS score of 5. Later, nasal swab for COVID RT-PCR tested positive. The patient was treated symptomatically with fluid replacement, optimization of electrolyte balance and oxygen supplementation. She had an uneventful recovery with gradual resolution of her abdominal and pulmonary symptoms. COVID-19 pathogenesis is believed to be mediated by the angiotensin converting enzyme 2 (ACE-2) receptor over the cell surface. ACE-2, which acts as a receptor for viral entry into host cells are highly expressed in pancreatic cells. All the reported cases of COVID-19 pancreatitis so far are known cases of COVID 19 pneumonia, developed acute pancreatitis or pancreatic injury in due course or during recovery of the illness. Ours is the first case to present with features of acute pancreatitis without any pulmonary symptoms, who turned out to be positive for COVID 19 during workup. Clinicians involved in the management of acute pancreatitis should be aware of its existence in the context of COVID-19. Further studies are needed to establish the real prevalence and clinical significance of pancreatic injury in COVID-19 patients.